Exploring Critical Discussion Research: A Bibliometric Analysis of Scopus-Indexed Publications - Rohimawati, Firly Aprilia; Shohib, Muhammad Wildan; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2023)
This study uses bibliometric analytic approaches to analyses all publications indexed in the Scopus database on critical discussion from 1929 to 2023 to trace the evolution and direction of critical discussion research on Scopus-indexed publications. The data obtained were analysed using Excel and R/R-Studio. VOSviewer analyses the simultaneous occurrence of keywords and document citations visually. The author found 502 publication data that match the function, subject, and criteria that have been set. The results of this study show an annual growth rate of 5.28%, with the publication of the most data in 2022 graphical analysis. The United States is the country that contributes the most publications affiliated with The University of British Columbia. Valcke, M. Become the most prolific writer in critical discussion themes. The bibliometric analysis performed was limited to Scopus data. Other national and international databases should have been considered in the study. This study presents a brief overview of the literature accessible to researchers working in education and provides recommendations for future research.